2013
DOI: 10.3758/s13421-013-0381-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for habituation of the irrelevant-sound effect on serial recall

Abstract: Working memory theories make opposing predictions as to whether the disruptive effect of task-irrelevant sound on serial recall should be attenuated after repeated exposure to the auditory distractors. Although evidence of habituation has emerged after a passive listening phase, previous attempts to observe habituation to to-be ignored distractors on a trial-by-trial basis have proven to be fruitless. With the present study, we suggest that habituation to auditory distractors occurs, but has often been overloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
87
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 45 publications
12
87
2
Order By: Relevance
“…An interesting aspect is that neither the foreknowledge provided in the present Experiments 1 and 2 nor the repeated presentation of upcoming distractors in previous studies (Bell et al, 2012;, 2014a, 2014b were sufficient to com pletely eliminate the disruption caused by auditory distractors. At first sight, this aspect may seem counterintuitive from the perspec tive of an attentional explanation of auditory distraction, which may be interpreted to imply that there should be a point at which distractors no longer attract any attention at all.…”
Section: Discussionmentioning
confidence: 87%
“…An interesting aspect is that neither the foreknowledge provided in the present Experiments 1 and 2 nor the repeated presentation of upcoming distractors in previous studies (Bell et al, 2012;, 2014a, 2014b were sufficient to com pletely eliminate the disruption caused by auditory distractors. At first sight, this aspect may seem counterintuitive from the perspec tive of an attentional explanation of auditory distraction, which may be interpreted to imply that there should be a point at which distractors no longer attract any attention at all.…”
Section: Discussionmentioning
confidence: 87%
“…) and hence the conclusions we have drawn from them. Röer et al (2014) found that discretely-presented sentences played forwards were no more disruptive of serial recall than the same sentences played backwards. The first thing to note is that this null effect, if taken at face value, poses a problem not only for our stimulus-specific relevance hypothesis but also for the predictability-based account because a sentence is clearly more predictable than the same sentence presented backwards.…”
Section: Discussionmentioning
confidence: 88%
“…Hence, the BF for alternative over null is .082, or strong evidence in favour of the null. 3 Note that some programmes (e.g., Rouder, Speckman, Sun, Morey, & Iverson, 2009) provide Bayes factors in favour of the null over the alternative hypothesis, and all comments about evidence Ͻ1/3 or Ͼ3 being strong evidence for one hypothesis over the other must be inverted. Likelihoods are provided here for readers who wish to make these inversions for themselves without rerunning the full Bayes factor analyses.…”
Section: Methodsmentioning
confidence: 99%